2012
DOI: 10.2341/10-337-l
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage of IPS Empress 2 Inlay Restorations Luted With Self-adhesive Resin Cements

Abstract: Although self-adhesive resin cements reduce the duration of the luting process, their universal practice requires caution because the microleakage performance of some brands is very poor. SUMMARYObjective: To assess the microleakage of three self-adhesive and one etch-and-rinse resin cements when luting IPS Empress 2 (Ivoclar Vivadent, Liechtenstein) all-ceramic inlay restorations to the prepared cavities in extracted human molars.Methods: The cylindrical Class V cavities were prepared on the buccal surfaces o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…reported that micro-leakage increased in self-adhesive cement as a result of TC 31) . This suggests that selfadhesive cement is sensitive to water absorption and thermal stress.…”
Section: Effect Of Storage Period and Thermal Cyclingmentioning
confidence: 99%
“…reported that micro-leakage increased in self-adhesive cement as a result of TC 31) . This suggests that selfadhesive cement is sensitive to water absorption and thermal stress.…”
Section: Effect Of Storage Period and Thermal Cyclingmentioning
confidence: 99%
“…Meanwhile, the use of SpeedCem produced significantly higher microleakage degree than Nexus 3. A recent study demonstrated that self-adhesive resin cements present higher microleakage scores than etch-and-rinse resin cement at enamel margins [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the inherently weak acidic nature of these monomers, the smear layer would not be removed, and hybrid layer and resin plugs in dentinal tubules would not be developed . Besides, their high viscosity and short contact time with the tooth before polymerization contribute to their higher microleakage level . Furthermore, differences in thermal expansion coefficients of the resin luting agent and the tooth/metal causes stresses at their junction with a potential for water infiltration during thermocycling .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Besides, their high viscosity and short contact time with the tooth before polymerization contribute to their higher microleakage level. 36,37 Furthermore, differences in thermal expansion coefficients of the resin luting agent and the tooth/metal causes stresses at their junction with a potential for water infiltration during thermocycling. 38 Furthermore, the hydrolysis of the bonding agent at the interface due to heat of the water bath during thermocycling could lead to water leakage due to nonpolymerized monomers.…”
Section: Discussionmentioning
confidence: 99%